Difficult encounters with a hemophilic patient: The inner perspective of physicians. (December 2014) - Vegni, Elena; Leone, Daniela; Biasoli, Chiara; Moja, Egidio A
This study aimed at exploring the hematologists' internal representation of a difficult encounter with a hemophilic patient, using a written open format. Narrations were analyzed with Interpretative Phenomenological Analysis. Three main issues were identified, each with sub-issues: (1) Inside the relationship : to tell or not to tell, the balance between a normal life and a deviant medical condition, the guilt; (2) The borders of the professional role : professional values, the "do-it-all" doctor; and (3) The existential confrontation . This study reveals the deep involvement of physicians with their patients, at a professional level and, strongly, at a personal level. The experience of being so deeply involved should be considered in the continuing medical programs for physicians dealing with hemophilia.